Air pollution intervention and life-saving effect in China. (April 2019) - Zou, Bin; You, Jiewen; Lin, Yan; Duan, Xiaoli; Zhao, Xiuge; Fang, Xin; Campen, Matthew J.; Li, Shenxin
Abstract: As a critical air pollutant, PM2.5 is proved to be associated with numerous adverse health impacts and pose serious challenges to human life. This situation is especially important for China as the most populous and one of the heaviest PM2.5 polluted country in the world. However, health burden estimations reported for China in previous studies may be biased due to the usage of PM2.5 concentrations at a coarsely spatial resolution, as well as the ignorance of the spatial discrepancies of parameters (e.g. respiratory rate) employed in the exposure-response function. This study therefore utilized a hybrid remote sensing-geostatistical approach to refine PM2.5 concentrations at 1 km resolution across mainland China from 2013 to 2017. Meanwhile, nationwide exposure parameters were for the first time introduced to weight the integrated exposure response (IER) function to calculate and spatially reallocate the corresponding PM2.5 -attributable premature deaths at 1 km resolution. Results showed that annually averaged PM2.5 concentrations in mainland China decreased by 39.5%, from 59.1 μg/m 3 in 2013 to 35.8 μg/m 3 in 2017. Subsequently, PM2.5 attributable premature deaths reduced 12.6%, from 1.20 million (95% CI: 0.57; 1.71) in 2013 to 1.05 million (95% CI: 0.44; 1.44) in 2017. This declining trend was found in most parts of China except some areas in Xinjiang, Jilin, and Heilongjiang provinces. As a result, 214, 821 (95% CI: 96, 675; 302, 897) life were saved with an estimated monetary value of US$ 210.14 billion (2011 values). However, it has to be acknowledged that, the central and northern China within priority areas of air pollution control were still experiencing high numbers of premature deaths due to the severe PM2.5 pollution and high-density population. But more worrying than these priority areas are those Harbin-Changchun Metropolitan Region, City Belt in Central Henan and Yangtze-Huaihe City Belt in non-priority areas, which also have been seriously suffering PM2.5 attributable premature deaths over 28, 000 cases per year. In conclusion, despite the huge gain in life-saving effects in China over the past five years with the help of air pollution intervention policy, future work on cleaner air and better human health is still strongly needed, especially in non-priority areas of air pollution control. Highlights: PM2.5 related premature deaths across China at 1 km resolution were estimated. Spatially refined premature deaths were reallocated with exposure enhanced IER model. Clean air action over the past five years received significant health benefits. Strategy for air pollution intervention is necessary in non-priority areas of China.